CULTURE SHOCK EXPERIENCED BY MAIN CHARACTER IN LAUREN KATE’S NOVEL “TORMENT” BY USING THE PSYCHOLOGY OF CULTURE SHOCK BY COLLEN WARD - Syahruni Junaid; Indah Pertiwi (Elite : English and Literature Journal, 2015)
Abstract This is a study which focuses on processes and affects of culture shock by main character in Lauren Kate’s novel “Torment” when she enters to new country through U-curve theory (the psychology of culture shock) by Collen Ward. The result shows that the phases of culture shock experienced by the main character are honeymoon, crisis, recovery and adjustment phase. There are two affects that is appeared through the phases of culture shock, they are the positive effects includes amazement, excitement, self confidence, good social interaction and life changes and negative effects including nervousness, fearness, confusion, feeling isolated and homesick.Abstrak Culture Shock pada Pemeran Utama dalam  Novel “Torment” karya Lauren Kate dengan Menggunakan Teori Psikologi Culture Shock oleh Collen Ward. Penelitian ini berfokus pada proses dan dampak dari culture shock yang dialami pemeran utama saat ia memasuki negara baru dalam novel “Torment” karya Lauren Kate. Penelitian ini menggunakan teori U-curve (psikologi culture shock) oleh Collen Ward. Hasil penelitian mengungkapkan bahwa tahapan culture shock yang dialami pemeran utama adalah tahap  honeymoon, crisis, recovery dan adjustment. Kemudian ada dua dampak yang dialami, yaitu dampak positif terdiri atas amazement, excitement, self confidence, good social interaction and life changes; dan dampak negatif yang terdiri dari  nervousness, fearness, confusion, feeling isolated dan homesick.